3D Model Based on Terrestrial Laser Scanning (TLS) Case study: The Cangkuang Temple, Garut District, West Java, Indonesia - Sadikin Hendriatiningsih; Deni Suwardhi; J. Januragadi (Journal of Engineering and Technological Sciences, 2015)
The subject of the  investigation reported in this paper is  the visualization of three-dimensional (3D) surface models in a 3D mapping survey using terrestrial laser scanning (TLS). The Cangkuang Temple nearby Garut City was chosen as the object. The laser technology instruments used were a Topcon GLS-1000 (Geodetic Laser Scanner) and a Topcon IS (Image Station). Twelve points at  the same position in each 3D surface model  were selected.  The coordinate system of the IS was then transformed into the coordinate system of the GLS-1000 using a 3D similarity transformation model. The 3D distances were calculated for each model.  Differences  in distance were considered as errors  in the x, y,  and z  direction.  The standard deviation of the  distance differences was ±0.301 m. Some of the distance differences did not fall within the range of tolerances (about 15%). The 3D surface model visualization of the Cangkuang Temple that was created from the GLS-1000 data was more precise than the one created from the IS data. In the future, such 3D surface model visualizations could be used for documentation, preservation and reconstruction of heritage buildings.